Analisis Gaya Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru Sekolah Dasar - Tihazanah, Tihazanah; Putra, Mulia; Sari, Siti Mayang (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this literature study aims to determine, explain and analyze the leadership style of school principals in improving teacher performance. The method for writing literature studies uses a conceptual research approach relating to ideas and theories. The stages in writing a literature study include selecting a topic, searching for literature, developing an opinion, and a literature survey. Data analysis used used content analysis. The results of the literature study found that the principal's leadership style in improving teacher discipline is a storytelling style. Apart from the storytelling style, the principal also applies a situational style. The principal's leadership style in improving teacher performance is a selling (consultative) style by directing teachers to complete duties, the principal's leadership style in improving teacher abilities, namely the participative style applied during internal teacher council meetings and other meetings and the principal's leadership style in increasing teacher responsibility, is a delegative style, namely dividing authority among members to carry out organizational tasks. It is hoped that supervisors and school principals can provide encouragement and direction in the work of discipline, commitment, ability and responsibility of teachers effectively and efficiently to improve performance in schools.